2013
DOI: 10.1186/scrt388
|View full text |Cite
|
Sign up to set email alerts
|

Autologous circulating angiogenic cells treated with osteopontin and delivered via a collagen scaffold enhance wound healing in the alloxan-induced diabetic rabbit ear ulcer model

Abstract: IntroductionDiabetic foot ulceration is the leading cause of amputation in people with diabetes mellitus. Peripheral vascular disease is present in the majority of patients with diabetic foot ulcers. Despite standard treatments there exists a high amputation rate. Circulating angiogenic cells previously known as early endothelial progenitor cells are derived from peripheral blood and support angiogenesis and vasculogenesis, providing a potential topical treatment for non-healing diabetic foot ulcers.MethodsA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Among healthy individuals without cardiovascular disease or diabetes, reduced CAC migration prospectively predicts greater carotid artery intima-media thickness (Keymel et al, 2008) and correlates with metabolic risk factors (Aschbacher et al, 2012a) and better endothelial function (Van Craenenbroeck et al, 2010). In animals, delivering CACs or CAC-conditioned media to sites of ischemic vascular injury can regenerate damaged tissue (Kalka et al, 2000; Di Santo et al, 2009; Ma et al, 2009; Toyama et al, 2012; O’Loughlin et al, 2013). Hence, CAC function is more than a “biomarker,” it is a mechanism of vascular repair.…”
Section: Introductionmentioning
confidence: 99%
“…Among healthy individuals without cardiovascular disease or diabetes, reduced CAC migration prospectively predicts greater carotid artery intima-media thickness (Keymel et al, 2008) and correlates with metabolic risk factors (Aschbacher et al, 2012a) and better endothelial function (Van Craenenbroeck et al, 2010). In animals, delivering CACs or CAC-conditioned media to sites of ischemic vascular injury can regenerate damaged tissue (Kalka et al, 2000; Di Santo et al, 2009; Ma et al, 2009; Toyama et al, 2012; O’Loughlin et al, 2013). Hence, CAC function is more than a “biomarker,” it is a mechanism of vascular repair.…”
Section: Introductionmentioning
confidence: 99%
“…O'Loughlin et al seeded autologous early endothelial progenitor cells onto collagen scaffolds. They observed that cells exposed to osteopontin accelerated the speed of wound closure along with increased angiogenesis [27]. It was noted that the wound Hydrogel-based biomaterials…”
Section: Hydrogel-based Biomaterialsmentioning
confidence: 99%
“…Fibrin [19] Collagen-GAG [20] Gelatin microcryogels [23] GAG [28] BLCC [29] Freeze-drying sponges pGIcNAc [18] Collagen sponge [27] Electrospun patches Collagen/PLGA [21] Silk fibroin [24] Biomaterials with controlledrelease of signaling molecules Nanoparticles loaded with GF/chemokines VEGF, bFGF nanoparticles in PEtU-PDMS/ fibrin [33] Curcumin loaded chitosan nanoparticles into collagen-alginate [36] With vectors encoding functional molecules AdeNOS in fibrin scaffold [37] Hyaluronic acid-MMP hydrogels with VEGF plasmids [34] GF/Chemokines preloadedd within Hydrogels Glucophage-loaded collagen/PLGA [21] Gelatin-PGA-based scaffold payload MCP-1 [35] healing benefit was associated with a more efficient vascular network. Breitbart et al seeded mouse dermal fibroblasts onto polyglycolic acid scaffold matrices, on which the cells were retrovirally transduced with the human platelet-derived growth factor B (PDGF-B) gene [28].…”
Section: High-water Content Hydrogelsmentioning
confidence: 99%
“…Studies using a variety of different cells have demonstrated that the addition of exogenous healthy cells can override the diabetes phenotype and enhance the regeneration of skin wounds . For example, using rodent models of diabetic skin ulcers, it has been demonstrated that the therapeutic ability of blood cells, in part, is due to the CD34+ cell population .…”
Section: Introductionmentioning
confidence: 99%